SOME REFLECTIONS ON THE ISLAMIZATION OF KNOWLEDGE - Majid, Arfah Abdul; Aljunied, Khairudin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
Since the 1970s, Muslim intellectuals have offered alternatives to Euro-American dominance in the realm of knowledge. A new movement known as the “Islamization of Knowledge” was founded arguing for an epistemological revolution that hinged on the ideals of Tawhid (unity) and the sacralization of “secularized” disciplines and subjects. This article offers some critical reflections on this intriguing undertaking. In our view, the Islamization of Knowledge project was structured primarily around the idea of civilizational difference and a partial reading of the history of knowledge formation. The notion that knowledge can be “Islamized” or has been “secularized” is equally problematic because human knowledge incorporates both secular and sacred dimensions. Duality exists only in the minds and practices of knowledge producers and policymakers.